Comparative analysis of vitamin status of schoolchildren in recreational period - L.V. Podrigalo; A.G. Platonova; M. Cieślicka (Physical Education of Students, 2013)
It is a comparative analysis of the characteristics of the vitamin status of schoolchildren during the summer recreation of 90th years of the last century and now. The study involved 167 schoolchildren aged 11-14 years. With the help of questionnaires developed by the authors assessed the severity of symptoms of vitamin deficiency, the prevalence of vitamin supplementation, frequency and volume of consumption of fruits and vegetables. It is confirmed that the saturation is the state of the vitamin in children is the best compared with data from 20 years ago, the state of multi-vitamin deficiency is replaced mono-vitamin deficit. The results, data evaluation and the availability of additional fortification of the diet of fruit and vegetables support the need for measures aimed at improving vitamin status. Using the questionnaire method is most appropriate for monitoring the vitamin status of schoolchildren.